The influence of developmental noise exposure on the temporal processing of acoustical signals in the auditory cortex of rats - Bures, Zbynek; Pysanenko, Kateryna; Syka, Josef (Hearing research, 2021)
Previous experiments have acknowledged that inappropriate or missing auditory inputs during the critical period of development cause permanent changes of the structure and function of the auditory system (Bures et al., 2017). We explore in this study how developmental noise exposure influences the coding of temporally structured stimuli in the neurons of the primary auditory cortex (AC) in Long Evans rats. The animals were exposed on postnatal day 14 (P14) for 12 minutes to a loud (125 dB SPL) broad-band noise. The responses to an amplitude-modulated (AM) noise, frequency-modulated (FM) tones, and click trains, were recorded from the right AC of rats of two age groups: young-adult (ca. 6 months old) and adult (ca. 2 years old), both in the exposed animals and in control unexposed rats. The neonatal exposure resulted in a higher synchronization ability (phase-locking) of the AC neurons for all three stimuli; furthermore, the similarity of neuronal response patterns to repetitive stimulation was higher in the exposed rats. On the other hand, the exposed animals showed a steeper decline of modulation-transfer functions towards higher modulation frequencies/repetition rates. Differences between the two age groups were also apparent; in general, aging had qualitatively the same effect as the developmental exposure. The current results demonstrate that brief noise exposure during the maturation of the auditory system influences both the temporal and the rate coding of periodically modulated sounds in the AC of rats; the changes are permanent and observable up to late adulthood.
Keywords: Animals; potkani Long-Evans; Time Perception; akustická stimulace; vnímání času; Rats, Long-Evans; sluchové korové centrum; hluk; sluchová percepce; Acoustic Stimulation; Noise; Auditory Cortex; Auditory Perception; krysa rodu Rattus; zvířata; Rats